PENGUASAAN TULISAN JAWI DI KALANGAN MAHASISWA PENGAJIAN ISLAM: KAJIAN DI INSTITUT PENGAJIAN TINGGI AWAM (IPTA) TEMPATAN - Abdul Hamid, Faisal@Ahmad Faisal; Abdullah, Niswa@Noralina (Journal of Al-Tamaddun, 2009)
Despite the endless efforts and campaigns carried out by the government and private agencies in order to bring back the interest of the community towards the national writing heritage, the results of these labours are yet to be seen. What makes the situation worse is the fact that the people who are capable of spreading the use of the Jawi writing have litte interest in doing so. These people refer to those with religious expertise, whether higher-level institution graduates or students who are yet to graduate. This research focuses on Islamic education graduates from the local universities who are randomly chosen from a number of IPTAs, in order to see the capabilities and uses of the Jawi writing in our daily life which will help measure the level of achievement in the efforts of bringing back the love of the people of the coutry towards the Jawi writing.